The discriminant power of biometrics for sex determination in European Bee-eaters Merops apiaster. Issue 1 (2nd January 2020) - Costa, Joana S.; Hahn, Steffen; Rocha, Afonso D.; Araújo, Pedro M.; Olano-Marín, Juanita; Emmenegger, Tamara; Alves, José A.
ABSTRACT: Capsule A combination of several biometric measures enables the reliable sexing of the European Bee-eater Merops apiaster, a species with subtle sex differences in plumage and morphometry. Aims To explore variation in biometrics and their suitability to discriminate sex in adult European Bee-eaters Merops apiaster . Methods We sampled populations of a long-distance migratory species with low sexual size dimorphism, the European Bee-eater Merops apiaster, from colonies in western Iberia (Portugal) and Central Europe (Germany) to investigate body size variation and derive population-specific and general sex discriminant functions. Results Overall, male Bee-eaters were larger than females while Bee-eaters from Germany and Portugal did not differ in size, except for primary length and tail length. The best single measurement to discriminate sex was wing length for Portuguese birds and tail tip length for German birds, as in the combined dataset. Multivariate discriminant functions of head-bill, wing and tail tip lengths provided the highest discriminant accuracy, discriminating sex for 91% of the birds from Portugal, 96% from Germany and 94% when using the combined dataset. Nonetheless, the discriminant accuracy remained high in the functions using only two variables for Portugal (head-bill and tail tip 91%, head-bill and wing 88%, wing and tail tip 88%), Germany (head-bill and tail tip 95%, wing and tail tip 97%) and in the combined dataset (head-bill and tail tip 92%, wing and tail tip 93%). Conclusions Population specific discriminant functions allow sexing of European Bee-eaters by morphometry with high degree of accuracy at least for Iberia and Central European populations. Such discriminant functions can be used to assign the sex of adult Bee-eaters reliably and swiftly while the bird is still in the hand, highlighting the potential of these functions for rapidly sexing species with low degrees of sexual size and plumage dimorphism.